THE LOW INTEREST OF INDONESIAN PEOPLE TO READ BOOKS - Angga Haikal Wahyudi; Muhammad Zul’Asfy Rayhan, Gloria Salsa Br Sembiring, Bunga Nailah Syam, Ermelia Verawaty Hutagalung (International Journal of Teaching and Learning, 2025)
Reading plays a crucial role in the intellectual and cultural development ofindividuals and societies. However, in Indonesia, the interest in reading books remains relatively low. This paper examines the factors contributing to the low reading interest among Indonesians, including socio-economic conditions, educational infrastructure, technological distractions, and cultural perceptions of reading. Data were gathered through surveys and literature reviews to provide a comprehensive understanding of the current state of reading habits in the country. The findings reveal that limited access to books, particularly in rural areas, the prevalence of digital entertainment, and a lack of encouragement from family and educational institutions are among the primary reasons for the low reading interest. Moreover, the study identifies strategies to promote a stronger reading culture, such as increasing public library access, integrating reading habits into school curricula, and utilizing digital platforms to make books more accessible. This research concludes that addressing the multi-faceted issues surrounding reading interest in Indonesia requires collaborative efforts from government, educators, and the community to foster a more literate and informed society.